The Role of Brown Adipose Tissue Dysfunction in the Development of Cardiovascular Disease - Chen, Hong-Jin; Meng, Ting; Gao, Ping-Jin; Ruan, Cheng-Chao (Frontiers in Endocrinology, 2021)
Brown adipose tissue (BAT), consisted of brown adipocytes and stromal vascular fraction, which includes endothelial cells, lymphocytes, fibroblasts and stem cells, plays a vital role in regulating cardiovascular health and diseases. As a thermogenic organ, BAT can influence body through strengthening energy expenditure by promoting glucose and lipid metabolism. In addition, BAT is also an endocrine organ which is able to secret adipokines in an autocrine and/or paracrine fashion. BAT plays a protective role in cardiovascular system through attenuating cardiac remodeling and suppressing inflammatory response. In this review, we summarize the advances from the discovery of BAT to the present and provide an overview on the role of BAT dysfunction in cardiovascular diseases.